Suspected adverse drug reactions reported for Brazilian children: cross-sectional study - Elisangela da Costa Lima; Guacira Corrêa de Matos; Jean M. de L. Vieira; Ivana C. da C.R. Gonçalves; Lucio M. Cabral; Mark A. Turner (Jornal de Pediatria, 2019)
Objective: To assess spontaneous reports of suspected adverse drug reactions in children aged 0–12 years from the Brazilian Health Regulatory Agency between 2008 and 2013. Methods: A cross-sectional study on suspected adverse drug reactions reports related to medicines and health products in children was carried out for a six-year period (2008–2013). Year of report, origin of report by Brazilian state, gender, age, suspected drug, adverse reaction description and seriousness were included in the analysis. The data obtained was compared to the number of pediatric beds in health services and to global data from the VigiBase (World Health Organization). Results: A total of 3330 adverse drug reactions were reported in children in Brazil in the investigated period (54% were in boys). About 28% of suspected adverse drug reactions reports involved 0 to 1-year-old children. Almost 40% of reports came from the Southeast region. Approximately 60% were classified as serious events. There was death in 75 cases. Nearly 30% of deaths involved off-label use; 3875 medicines (465 active substances) were considered suspected drugs. Anti-infective (vancomycin, ceftriaxone, oxacillin, and amphotericin), nervous system (metamizole) and alimentary tract and metabolism medicines were more frequent in reports. Conclusions: The distribution of suspected adverse drug reactions reports by sex and age group corresponded to the profile of children hospitalized in Brazil. Data about seriousness and medicines reported may be useful to encourage regulatory actions and improve the safe use of medicines in children. Resumo: Objetivo: Analisar relatos espontâneos de suspeitas de Reação Adversa a Medicamento (RAM) em crianças de 0 a 12 anos notificadas pela Agência Nacional de Vigilância Sanitária entre 2008 e 2013. Métodos: Um estudo transversal a partir de notificações de suspeitas de RAM relacionadas a medicamentos e produtos para a saúde em crianças foi realizado por um período de seis anos (2008-2013). O ano da notificação, a origem do relato por estado brasileiro, sexo, idade, o medicamento suspeito, a descrição da reação adversa e a gravidade foram incluídos na análise, bem como o número de leitos nos serviços de saúde e dados global da VigiBase. Resultados: Um total de 3330 reações adversas foram relatadas em crianças no Brasil no período investigado (54% em meninos). Cerca de 28% dos relatos de suspeitas de RAM envolveram crianças de 0 a 1 ano de idade. Quase 40% dos relatos vieram da região Sudeste. Aproximadamente 60% foram classificados como eventos graves. Houve ocorrência de morte em 75 casos. Quase 30% das mortes envolveram o uso off-label dos medicamentos. Um total de 3875 medicamentos (465 substâncias ativas) foram considerados fármacos suspeitos. Medicamentos anti-infecciosos (vancomicina, ceftriaxona, oxacilina e anfotericina), com ação no sistema nervoso (dipirona) e no trato digestivo foram os mais frequentemente notificados. Conclusões: As notificações de suspeitas de RAM por sexo e faixa etária corresponderam ao perfil de crianças hospitalizadas no Brasil. Os dados sobre gravidade e medicamentos relatados podem ser úteis para encorajar ações reguladoras e melhorar o uso seguro de medicamentos em crianças. Keywords: Adverse reactions, Children, Pediatrics, Database study reporting, Drug monitoring, Pharmacoepidemiology, Palavras-chave: Reações adversas, Crianças, Pediatria, Relato de estudo de banco de dados, Monitoramento de medicamentos, Farmacoepidemiologia